Functional Role of Odorant-Binding Proteins in Response to Sex Pheromone Component Z8-14:Ac in Grapholita molesta (Busck) - Yuqing Luo; Xiulin Chen; Shiyan Xu; Boliao Li; Kun Luo; Guangwei Li (Insects)
The plum fruit moth (PFM), Grapholita funebrana, and the oriental fruit moth (OFM), G. molesta, are closely related fruit moth species that severely damage fruit trees in Rosaceae. Both species share common primary sex pheromone components Z8-12:Ac and E8-12:Ac. The secondary sex pheromone components of PFMs consist of Z8-12:OH, Z8-14:Ac, and Z10-14:Ac, while those of OFMs include Z8-12:OH and 12:OH. Previous researchers have proved that the inclusion of Z8-14:Ac and Z10-14:Ac did not augment PFM catches but inhibited OFM catches in orchards in Europe, thereby maintaining the species-specificity of the PFM sex attractant. However, which of these components, Z8-14:Ac or Z10-14:Ac, plays the major role in inhibiting OFM attraction remains unclear. In the current study, electroantennogram (EAG) assays indicated that both OFM and PFM males exhibited a moderate EAG response to Z8-14:Ac and Z10-14:Ac. Rubber septa loaded with varying ratios of Z8-14:Ac (1% to 30%) or Z10-14:Ac (5% to 110%) combined with a constant dose of Z8-12:Ac and E8-12:Ac produced diverse trapping effects. Sex attractants containing Z8-14:Ac did not significantly affect the trapping of PFM males but drastically reduced the capture of OFM males, with the reduction reaching up to 96.54%. Attractants containing more than 10% of Z10-14:Ac simultaneously reduced the number of OFM and PFM males captured. Z8-14:Ac was indispensable for maintaining the specificity of sex pheromones. Fluorescence competitive binding assays of recombinant GmolPBP2 showed the lowest Ki value (0.66 ± 0.02 μM) among the PBPs/GOBPs from OFMs, suggesting that it is the most likely target for Z8-14:Ac. Molecular dynamic simulation and site-directed mutagenesis assays confirmed that the Phe12 residue, which forms a π–alkyl interaction with Z8-14:Ac, was crucial for GmolPBP2 binding to Z8-14:Ac. In conclusion, Z8-14:Ac is vital to the specificity of PFM sex pheromones inhibiting OFM attractants when added to Z8-12:Ac and E8-12:Ac. This could be potentially used to develop species-specific sex attractants for the PFM.